Budgetary Policy as a Tool of Macroeconomic Regulation of the Economy and Social Sphere - SELEZNEV, Aleksandr Zaharovich; CHEREDNICHENKO, Larisa Gennadievna; DUBOVIK, Mayуa Valerianovna; SIGAREV, Aleksandr Victorovich (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
Goal of the study. Analysis of the budget system of the Russian Federation, identification of its role in the mechanism of centralized macroeconomic regulation of economic and social processes. Methodology. The paper presents the practice of using the strategic budget planning in developed countries, its advantages and disadvantages, budget planning schemes applied in the Russian Federation. Results. Budgetary policy in the Russian Federation has been critically interpreted on the basis of four different budget models. Changes in the mechanism of centralized financial regulation in the process of development of the budget system have been identified and evaluated. Realities of budget three years plans in terms of structural crisis and sanctions against Russia have been analyzed. Risks of the Russian budget balance have been assessed. Necessity of expanding the social orientation of budgetary policy has been justified. Conclusions and significance. Budget planning in the format of ‘three-year plans’ (except 2009) during eight years (2008-2015) turned out to be imitation of planning. Identified trends in the development of the budget system of Russia indicate narrowing human-centricity of the Russian budget model and pose a threat to the implementation of constitutional provisions on the sociality of the state. At a large share of oil and gas revenues in the budget revenues and the cyclicality of their dynamics, the significance of creation and more efficient use of sovereign wealth funds is preserved and increased. Justification of academic novelty. Budget planning in Russia has been critically interpreted in view of the impossibility of the development of a realistic forecast of macroeconomic indicators of socio-economic development in conditions of significant influence of external macroeconomic shocks on the revenue part of budget, due to the high volatility of commodity and currency markets, as well as global economic and political conditions.